Digital light processing (DLP)‐based (bio)printing strategies for tissue modeling and regeneration. Issue 2 (3rd October 2022) - Li, Hongbin; Dai, Jiliang; Wang, Zixuan; Zheng, Heshan; Li, Wanlu; Wang, Mian; Cheng, Feng
Abstract: Digital light processing (DLP)‐based bioprinting technology has recently aroused considerable concerns as a strategy to deliver biomedical materials and/or specific cells to create sophisticated structures for various tissue modeling and regeneration. In this review, we display a concise introduction of DLP bioprinting, and a further discussion on the design and manufacture of DLP (bio)printer with varied bioinks and their biomedical applications toward drug screening, disease modeling, tissue repair, and regenerative medicine. Finally, the advantages, challenges, and perspectives of the DLP printing platforms are detailed. It is believed that DLP bioprinting will play a decisive role in the field of tissue model and regenerative medicine, mainly due to its time‐efficient, higher resolution, and amenability to automation for various tissue needs. Abstract : The field of DLP bioprinting has been exploited for a wide range of applications in tissue repair, tissue regeneration, disease modeling and drug screening.